A systematic literature review of the effectiveness of occupational health and safety regulatory enforcement. Issue 11 (7th June 2016) - Tompa, Emile; Kalcevich, Christina; Foley, Michael; McLeod, Chris; Hogg‐Johnson, Sheilah; Cullen, Kim; MacEachen, Ellen; Mahood, Quenby; Irvin, Emma
Abstract : Background: We aimed to determine the strength of evidence on the effectiveness of legislative and regulatory policy levers in creating incentives for organizations to improve occupational health and safety processes and outcomes. Methods: A systematic review was undertaken to assess the strength of evidence on the effectiveness of specific policy levers using a "best‐evidence" synthesis approach. Results: A structured literature search identified 11, 947 citations from 13 peer‐reviewed literature databases. Forty‐three studies were retained for synthesis. Strong evidence was identified for three out of nine clusters. Conclusions: There is strong evidence that several OHS policy levers are effective in terms of reducing injuries and/or increasing compliance with legislation. This study adds to the evidence on OHS regulatory effectiveness from an earlier review. In addition to new evidence supporting previous study findings, it included new categories of evidence–compliance as an outcome, nature of enforcement, awareness campaigns, and smoke‐free workplace legislation. Am. J. Ind. Med. 59:919–933, 2016. © 2016 Wiley Periodicals, Inc.